1964
DOI: 10.2307/1934943
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific Transfer of Ca‐45 and P‐32 by Root Systems

Abstract: The extent and rate of interspecific translocation of P—32 and Ca—45 were determined when radiosotopes introduced into stumps of seven red maples were found in leaves of 19 other species which were up to 24 ft from the donor maples. The mode of interspecific transfer may be either by exudation from the donor and absorption by the acceptor species or through mutually shared mycorrhizal fungi. Root grafting probably is not important in transfer. The importance of recognizing the root mass of an ecosystem as a fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1967
1967
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…Such transfer could involve two live plants but may also occur between senescent and live roots of the same plant, different plants of the same species, or plants of different species. Woods and Brock (1964) injected tree stumps with radioactive Ca and P and recovered isotope in nearby vegetation, but this experiment is open to considerable criticism since dying roots attached to the tree stumps would certainly release isotope into the soil, where it could be picked up by the soil mycelium in the normal way. More recently, Read et al (1979) claimed to have demonstrated transfer of 32p between Plantago and Festuca spp.…”
Section: Competition Between Species In Mixed Communitiesmentioning
confidence: 99%
“…Such transfer could involve two live plants but may also occur between senescent and live roots of the same plant, different plants of the same species, or plants of different species. Woods and Brock (1964) injected tree stumps with radioactive Ca and P and recovered isotope in nearby vegetation, but this experiment is open to considerable criticism since dying roots attached to the tree stumps would certainly release isotope into the soil, where it could be picked up by the soil mycelium in the normal way. More recently, Read et al (1979) claimed to have demonstrated transfer of 32p between Plantago and Festuca spp.…”
Section: Competition Between Species In Mixed Communitiesmentioning
confidence: 99%
“…These constellations of hyphal bridges among root systems have been suggested to be pathways for inter-plant movement of fixed-carbon by both ECM [21] and AM [22] fungi, mineral nutrients such as nitrogen [23], [24] and phosphorus [25], [26] by both types of mycorrhizal fungi, and water, the latter especially by ECM networks [27].…”
Section: Introductionmentioning
confidence: 99%
“…These linkages allow for carbon and nutrient transfer between tree species and could play an important role in ameliorating light competition and sharing scarce resources (Woods and Brock 1964;Finlay and Read 1986;Perry et al 1989;Simard et al 1997a). These linkages allow for carbon and nutrient transfer between tree species and could play an important role in ameliorating light competition and sharing scarce resources (Woods and Brock 1964;Finlay and Read 1986;Perry et al 1989;Simard et al 1997a).…”
Section: Introductionmentioning
confidence: 99%